Managing the safety of nature? Park visitor perceptions on risk and risk management. Issue 3 (3rd July 2022) - Gstaettner, A. M.; Rodger, K.; Lee, D.
ABSTRACT: An important focus of risk management in national parks is the interplay between how risk is perceived and how visitors would like risks to be managed. This paper presents the results of a study that investigated visitors' expectations on how the risk of injury should be controlled by park management agencies, linking it with perceptions on park dangerousness and confidence to deal with unexpected adverse events. Results of our survey among visitors in two Western Australian national parks, Karijini and Stirling Range, suggest that visitors tend to approve risk management intervention. However, higher levels of risk control were linked to a lower likelihood that visitors thought that the park was dangerous. Visitors establish a sense of safety from the park management context when the park appears to be managed well. Given that national parks are never free of risk, the management challenge is to balance legal and moral obligations along with societal expectations, without reducing visitors' appreciation of risk.